Genotype Affected Callus Induction and Plant Regeneration from Dehusked Rice (Oryza sativa L.) Seeds (The Agriculturists, 2010)
Callus induction and plant regeneration ability of the dehusked rice genotypes are important tools for varietal improvement. This investigation presents the comparative callus induction and plant regeneration as obtained from the dehusked seeds of rice cultured on MS (Murashige-Skoog) medium. In the experiment conducted in a Complete Randomized Design under laboratory conditions, dehusked seeds of Ranisalute, Chiniatap, Somudrafena, Chiniguri-2 and Katchra rice cultivars grown in South West Bangladesh were tested on autoclaved and agarified MS nutrient medium with four replications to study their callus induction and subsequent plant regeneration ability. Chiniguri-2 yielded the highest calli and plant regeneration.